Influence of team's rank on soccer referees' external and internal match loads during official matches - Castillo, D.; Castagna, C.; Cámara, J.; Iturricastillo, A.; Yanci, J. (The Journal of Strength and Conditioning Research, 2018)
The aim was to examine the external and the internal match loads (ML) of field referees (FRs) attending teams of different ranking during championship matches. Twenty FR who officiated in 30 official soccer matches (30 observations) participated in our study. The criteria for allocating the soccer referees' ML results were based on the teams' final league positions as follows: matches performed by Top 10 teams (TOP10), matches performed by bottom 10 teams (BOT10), and matches played among TOP10 and BOT10 teams (MIXED). External (match activities, accelerations [Acc], and decelerations [Dec]) and internal MLs (Edwards' heart rate [HR]-derived training impulse [TRIMPEDW], HRmean expressed as a percentage of HRpeak [%HRpeak], and differentiated rating of perceived exertion [dRPE]) were recorded. The main results showed that FR, who officiated TOP10 matches, covered more distance at a low walking speed (<3.6 km/h) and performed a higher percentage of high-intensity accelerations and decelerations than those FR who officiated lower ranked teams' matches. Moreover, FR who officiated MIXED matches registered lower values of TRIMPEDW MLs and %HRpeak and declared higher respiratory (sRPEres ML) and muscular (sRPEmus ML) perceived MLs during the second half. Considering those FR who officiate matches between teams of a higher competitive level will need to produce higher match responses, especially regarding the percentage of distance covered at high intensity, accelerations, and decelerations; physical trainers of soccer referees at a high competitive level should implement these high-intensity short-term actions in specific training regimes.